If a tree falls a story of the Earth Liberation Front - Curry, Marshall; McGowan, Daniel G. (New York, NY : Oscilloscope Pictures, 2011)
Profiles the radical environmental organization ELF and Oregon-based member Daniel G. McGowan, who faced possible life imprisonment for his related activities, while addressing various perspectives on environmentalism, activism, and terrorism.
Originally released as a motion picture in 2011.
Features: audio commentary; deleted scenes; extended interviews.
Not rated.
DVD, Dolby digital stereo.
Keywords: McGowan, Daniel G; Earth Liberation Front; Ecoterrorism; Green movement; Environmentalism; Environmental protection -- Citizen participation; Environmental films; Documentary films; Nonfiction films